2015
DOI: 10.1002/2014jd022654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of new aircraft observations Mode‐S MRAR in a mesoscale NWP model

Abstract: The impact of recently available high-resolution Mode-S Meteorological Routine Air Report (MRAR) wind and temperature observations is evaluated in the mesoscale numerical weather prediction (NWP) model Aire Limitée Adaptation dynamique Développement InterNational (ALADIN). Data available from the airspace communicating with the Ljubljana Airport in Slovenia are assimilated by using the three-dimensional variational assimilation procedure on top of all other observations assimilated operationally. A data select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…The results above explain the verification scores of Strajnar et al (), who assimilated Mode‐S observations and demonstrated positive scores when using Mode‐S for verification, but neutral impact when using radiosondes for verification (their Figures and ). Also, their results for the summer period are less positive than the winter period, possibly because the latter contains a stable high pressure period with reduced advection, thus yielding higher correlations between increments and evolved increments.…”
Section: Observation Impact Assessmentsupporting
confidence: 69%
See 1 more Smart Citation
“…The results above explain the verification scores of Strajnar et al (), who assimilated Mode‐S observations and demonstrated positive scores when using Mode‐S for verification, but neutral impact when using radiosondes for verification (their Figures and ). Also, their results for the summer period are less positive than the winter period, possibly because the latter contains a stable high pressure period with reduced advection, thus yielding higher correlations between increments and evolved increments.…”
Section: Observation Impact Assessmentsupporting
confidence: 69%
“…That is, model forecast quality is not uniform over the verification area and forecast skill scores highly depend on the sampling of the verifying observing system. This explains the inconsistent skill scores found in Strajnar et al (2015) and to a less extent in de Haan and Stoffelen (2012) who assimilated Mode-S EHS in their respective mesoscale models and showed better skill scores when verifying against Mode-S EHS rather than against radiosondes. The results demonstrate that one has to be careful when using observations for forecast verification when assessing the added value of new observing systems for NWP.…”
Section: Summary Discussion Conclusion and Outlookmentioning
confidence: 85%
“…The physics package used in the model uses Modular, Multi-scale, Microphysics and Transport (3MT) structure (Gerard et al, 2009). Initial conditions for the model are provided by atmospheric analysis with 3-hourly threedimensional variational assimilation (3D-Var) (Fischer et al, 2005;Strajnar et al, 2015) and optimal interpolation for surface and soil variables. Most of the conventional and satellite observations are assimilated, including surface stations (Synop) and ship reports, radiosondes, Automated Meteorological Data Relay (AMDAR), atmospheric motion vectors (AMV), Advanced Microwave Sounding Unit (AMSU)-A and -B, Metop-A and -B polar orbiters and water vapor channels from the geostationary Meteosat Second Generation Spinning Enhanced Visible and Infrared Imager (SE-VIRI).…”
Section: Introductionmentioning
confidence: 99%
“…Strajnar et al (, fig. ) showed that meteorological routine air reports (MRAR) of ambient temperature, obtained from the secondary surveillance radar (SSR) using Mode‐S, centred around Ljubljana airport, Slovenia, have a spatial and temporal resolution sufficient to locate a temperature inversion at around 1,000 m above the surface.…”
Section: Introductionmentioning
confidence: 99%